PENGARUH PEMBERIAN EKSTRAK BUAH APEL DAN PUPUK NPK TERHADAP PERTUMBUHAN BATANG ATAS OKULASI DURIAN THE EFFECT OF APPLE EXTRACT AND NPK FERTILIZER ON GROWTH OF UPPER STEM DURIAN OCULATION - Anwar, A.H. Syaeful; Iqbal, Achmad (Pembangunan Pedesaan, 2010)
The aim of the research was to know 1) the effect of apple solution and NPK fertilizer on the upper stem of durian brown oculation and 2) the interaction between the solution and the fertilizer on the upper stem. This research was carried out in the research experiment station, Agriculture Faculty, Jenderal Soedirman University, Purwokerto. Randomized Completely Block Design (RCBD) was used with 4 x 3 factorial repeated four times. The first factor was apple solution concentration consisted of four levels, i.e. 0, 10, 15, and 20 g per liter; the second one was dosage of NPK fertilizer consisted of three levels, i.e. 7.5, 12.5, and 17.5 g per plant. Data of variable observed were analyzed by F test continued with Least Significant Differences Test at five percent level of significant and regression analyses if needed. Result of this research showed that the apple solution significantly affected oculation sprout stem number. NPK fertilizer did not affect oculation of the stem. Interaction between given apple solution and the fertilizer to brown oculation of the stem did not significant differ. Concentration of 15 g/L from the solution could increase the number of durian brown oculation sprout.